Developing a customer loyalty programme : A case study of Hock Theng Trading / Peter L. Enchana - Enchana, Peter L. (2003)
Hock Theng Trading Sdn. Bhd. is one ofthe main companies in Sarawak that cater to the signage needs of the business community in the state. Their client comes from such diverse industries like the manufacturing, service-oriented, retail, local/state and federal government. However, the company does encounter problems like lack of repeat customers and conversion of potential customers into clients. As such, the study looked into the relationship between the firm and it clients and also those that did not use its service. Among the objectives of the Paper was to determine factors that enhance and hinder the relationship, suggest how to retain clients and thereafter develop a customer loyalty programme.